Preliminary squid survey in coastal waters off Kuala Terengganu, Malaysia - Shahardin, Zainal Ashirin; Ibrahim, Abdul R. (Asian Fisheries Society, 1992)
A survey on squid catches was dine in coastal waters off Kuala Terengganu, Terengganu, Malaysia, in 1989 and 1990. Data were taken from three gears: two commercial boats employing jigs and a purse seine, respectively, and a newly developed squid net. Fishing operations were carried out in open water during moonless nights. Emphasis was placed on the catch of the two most common and dominant squids found in the area, Loligo chinensis and Loligo sibogae. It was found that both L. chinensis and L. sibogae can be caught throughout the water column by the purse seine while mainly L. sibogae was obtained from near surface by the squid net. Jigs caught only L. chinensis and these were much bigger than the same species taken by the other two gears.